2018
DOI: 10.1002/hpm.2678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the technical efficiency of the forms of hospital management based on public‐private collaboration of the Madrid Health Service, as compared with traditional management

Abstract: SummaryFundamentalsThe study aims to carry out a comparative analysis of the technical efficiency of hospital management based on public‐private collaboration, as compared with traditional management. Specifically, we compare traditionally managed public hospitals, public hospitals managed by a private finance initiative (PFI), public hospitals managed through a public‐private partnership (PPP), and hospitals managed through other forms of management, during the period 2009 to 2014, in the hospitals dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Even if the concept itself is interesting and potentially advantageous both to the public sphere and the private sector when it is well designed, 3 well managed and well controlled, the practical results did not translate into value gains, especially to the public entity, harming public interest. In fact, some authors claim that healthcare PPPs are more technically efficient than traditionally managed institutions 35 . Still, everything leads one to believe that the existence of healthcare PPP in Portugal was exclusively because of political reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Even if the concept itself is interesting and potentially advantageous both to the public sphere and the private sector when it is well designed, 3 well managed and well controlled, the practical results did not translate into value gains, especially to the public entity, harming public interest. In fact, some authors claim that healthcare PPPs are more technically efficient than traditionally managed institutions 35 . Still, everything leads one to believe that the existence of healthcare PPP in Portugal was exclusively because of political reasons.…”
Section: Resultsmentioning
confidence: 99%
“…A unique evidence provides clues about efficiency of city hospitals build with public-private partnership models in Madrid Health Service. It has been stated that greater efficiency is obtained from public-private collaboration models than in traditionally managed hospitals (Franco Miguel et al, 2019). As far as we know, there are no existing studies about the efficiency of large city hospital investments in Turkey.…”
Section: Introductionmentioning
confidence: 98%
“…Efficiency is obtaining maximum output through minimum effort or cost (Atmaca, Turan, Kartal, & Çiğdem, 2012). There are two main most commonly implemented methods in the world to measure efficiency of hospitals: parametric and non-parametric methods (Franco Miguel, Fullana Belda, & Rua Vieites, 2018) The parametric method, which is represented by Data Envelopment Analysis (DEA), is based on linear programming and is used to measure relative efficiency of hospitals with multiple inputs and multiple outputs (Daraio C & L., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The review of literature has revealed that most of the DEA method-based relevant efficiency analyses on hospitals are based on non-financial input and output variables. While the number of health-care employees (such as doctors, assistants, nurses, auxiliary health-care workers) and the total number of beds are used as input variables, the number of outpatients, inpatients, and discharged patients, hospital bed occupancy rate, hospital bed turnover rate, the total number of hospitalization days, the total number of surgical operations, and hospital death rates are used as output variables (Atmaca et al, 2012;Bayraktutan & Pehlivanoğlu, 2012;Franco Miguel et al, 2018;Gülsevin & Türkan, 2012;Kutlar & Salamov, 2016;Li & Dong, 2015;Yiğit, 2016) There are also studies in the literature, although not many, which defined inputs and outputs based on both financial and non-financial data or based only on financial data to measure performances of health care enterprises through DEA method. In such studies, total expenses variable is used as an input variable in addition to variables of specialist physicians, practitioners and the total number of hospital beds, whereas total income is used as an output variable in addition to the variables of outpatients, major surgeries, and the number of hospitalization days (Bal, 2013;Czypionka, Kraus, Mayer, & Rohrling, 2014;Temur, 2010;Temür & Bakırcı, 2008).…”
Section: Introductionmentioning
confidence: 99%